DARI PENUTUPAN TPA MENUJU KEBIJAKAN IKLIM: PERSEPSI PUBLIK DAN KOMUNIKASI KEBIJAKAN DALAM TRANSISI TATA KELOLA SAMPAH DI BALI - Rian Prayana, I Kadek (Penerbit Lafadz Jaya, 2025)
The closure of the Suwung Landfill (TPA Suwung) in Bali in August 2025 marked a critical juncture in Indonesia’s urban waste governance, signaling a policy shift toward source-based waste management (reduce–reuse–recycle). While the policy aligns with global methane mitigation targets and the circular economy (CE) agenda, its rapid implementation, limited transitional planning, and the Governor’s assertive communication style have triggered public controversy. This study investigates public perception and policy communication surrounding the TPA Suwung closure, drawing on qualitative analysis of policy documents, media reports, and field interviews in selected TPS3R and TPST facilities. Findings reveal a substantial policy–capacity gap: despite regulatory support (Provincial Regulation No. 47/2019; Governor’s Circular No. 9/2025) and the construction of new TPST facilities, infrastructure coverage remains insufficient, with most daily waste still unprocessed at the source. Public responses, amplified through social media, indicate perceptions of distributive and procedural injustice, especially when the burden of waste processing shifts abruptly to households and businesses without adequate technical and logistical support. This paper contributes to the waste governance literature by demonstrating how policy communication mediates the acceptance of environmental reforms in the Global South and by framing urban waste policy as a climate-relevant intervention. The results underscore the need for participatory policy design, equitable burden-sharing, and evidence-based transitional roadmaps to prevent unintended environmental and social consequences.